A história em corpos interpretativos: o ensino de História pela dança e o teatro - MELO, Felipe Araújo de (2022)
The objective of this study is to reflect on the production of a methodology for teaching history through dance and theater. This research was developed from the extension project "Teacher Training Processes: Teaching and Learning Actions in History", at the Federal University of Pará - UFPA. The focus of the project was to give history tutoring using new teaching resources such as music, didactic games, and audiovisual materials. The dynamics consisted in accompanying the teacher or teacher responsible for the class, identifying the content being worked on, and during the teachers' vacant schedules, offering the tutoring classes. This research was developed in the period 2018-2021, and targeted the institution Escola Municipal de Ensino Fundamental José Maria Moraes e Silva, in the city of Ananindeua/Pará. During the course of the research, two pilot experiences were carried out, which provided the application of history teaching through dance and theater. Through the ethnography of the teaching practice, as a methodology, it was possible to develop several registers such as field diaries, photographs, and drawings, which listed the students' bodies as an object of investigation and became a source of analysis to understand the school routine and its implications in the application of the methodological proposal. The research takes into consideration: What knowledge is necessary to teach history through dance and theater; School Culture, Body Controls and Subversions, the body at school; and finally, Historical Consciousness through Dance and Theater. In this research, teacher education is also problematized, instigating that training courses for future history teachers understand the need for an interdisciplinary curriculum between history, dance, and theater. What is addressed here is a history teaching based on the practice of the dancing and theatrical body, in which knowledge is developed together with the students.